Novel vectors for functional interrogation of Xenopus ORFeome coding sequences. Issue 10 (12th August 2019) - Sterner, Zachary R.; Rankin, Scott A.; Wlizla, Marcin; Choi, Jinyoung A.; Luedeke, David M.; Zorn, Aaron M.; Buchholz, Daniel R.
Abstract: The current Xenopus ORFeome contains ~10, 250 validated, full‐length cDNA sequences without stop codons from Xenopus laevis and ~3, 970 from Xenopus tropicalis cloned into Gateway‐compatible entry vectors. To increase the utility of the ORFeome, we have constructed the Gateway‐compatible destination vectors pDXTP and pDXTR, which in combination can control the spatial and temporal expression of any open reading frame (ORF). pDXTP receives a promoter/enhancer of interest, which controls the spatial expression of a doxycycline‐inducible transcription factor rtTA. pDXTR receives an ORF of interest, which is controlled by a tetracycline response element enabling temporal control of ORF expression via rtTA activation by simple addition of doxycycline to the rearing water at any desired time point. These vectors can be integrated into the genome via well‐established microinjection‐based SceI, tol2, or phi‐C31 transgenesis procedures and contain fluorescence reporters to confirm transgene integration. Cell‐autonomous verification of ORF expression occurs via red nuclear fluorescence due to an mCherry‐histone H2B fusion protein that is cleaved from the ORF during translation. Function of all essential features of pDXTP and pDXTR has been experimentally validated. pDXTP and pDXTR provide flexible molecular cloning and transgenesis options to accomplish tissue‐specific inducible control of ORF expression in transgenic Xenopus .